(untitled) (Texas Journal of Engineering and Technology, 2024)
By-products are internal organs and body parts obtained during the processing of farm animals. Depending on the type of animal, it is divided into by-products from cattle, sheep, goats and pigs. Depending on the use, by-products are divided into consumable and used for technical needs. Technical byproducts include: reproductive organs, skin, horns, wool. Consumed by-products include meat products, important in human life. By-products are perishable, so they must be processed quickly, within 3 hours. Our article describes the production of additional products.